PENGARUH PLASTIK PENGEMAS Low Density Polyethylene (LDPE), High Density Polyethylene (HDPE)DAN Polipropilen (PP)TERHADAP PENUNDAAN KEMATANGAN BUAH TOMAT (Lycopersicon esculentum.Mill ) - Johansyah, Afrazak; Prihastanti, Erma; Kusdiyantini, Endang (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
The increasing demand of tomatoes corresponds to the economic and population growth. To maintain the quality of tomatoes, an effort to holdup the tomato ripeness was done using several kinds of plastic packaging. This research was intended to assess the effects of using plastic packaging and the most effective kind of plastic packaging to extend tomato storage period. The research was done at BSFT Biology Laboratory Diponegoro University and Food Technology Laboratory Soegijapranata Catholic University.    The design used in the research was Completely Randomized Design (CRD) with some treatments using different  plastic packaging type (P 0 = control / without packaging, P1 = Low Density Polyethylene (LDPE), P2 = High Density Polyethylene (HDPE) and P3 = Polypropylene (PP), each treatment was repeated three times. The parameter observed was the percentage of weight loss, the change in color (using chromameter method); the hardness level (texture analyzer method) and total content of sugar. Data were analyzed by Analysis of Variance (ANOVA) then continued with Duncan's Multiple Range Test (DMRT) at the 95% significance level to find out the difference. The results show that the use of plastic as packaging materials is able to delay tomato ripeness and the effective type plastic-based packaging to weight loss and change color is HDPE and PP.